Pengaruh Penggunaan Cashless dan Online Shopping Terhadap Perilaku Konsumtif Gen Z - Dina Cahyani; Acep Suherman; Iqbal Noor (Masyarakat Ekonomi Syariah Bogor, 2024)
This study aims to determine and explain the effect of the use of Cashless and online shopping on the consumptive behavior of students of the Faculty of Economics, Muhammadiyah University of Sukabumi. This research uses an associative quantitative method by collecting data through distributing questionnaires. The population in this study were students of the Faculty of Economics, University of Muhammadiyah Sukabumi. The sample was taken randomly using the slovin formula, regardless of population strata. The questionnaire has been tested for validity and reliability. The research data used Classical Assumption analysis techniques (Normality Test, Multicollinearity Test, Heteroscedasticity Test) Multiple linear analysis tests, hypothesis testing (T Test and F Test) and using the Coefficient of Determination Test. The results of the one sample kolmogoroov-smirnov test (normality test) show that the significance value of 0.190 is greater than 0.05, it can be concluded that the residual values are normally distributed. The results of hypothesis testing using the t test show that the t value of variable X1 is 0.128 < 1.662 so there is no influence and insignificance between the use of Cashless and consumptive behavior, this shows that Ha is rejected and Ho is accepted, the t test of variable X2 shows that the t count of 3.734> 1.662 indicates that there is an influence of online shopping on consumptive behavior, so Ha is accepted and Ho is rejected. The results of the F test show that f count is 7.674> f table 3.10 with a significance of 0.000 <0.05, which means that Ha is accepted and Ho is rejected. Therefore, it can be concluded that the independent variables simultaneously have a significant effect on income levels. The test results of the coefficient of determination of variable Y amounted to 15% while 85% was influenced by other factors. It can be concluded that the use of Cashless and Online Shopping has a positive and significant effect on Gen Z Consumptive Behavior (Students of the Faculty of Economics, University of Muhammadiyah Sukabumi